Análise histomorfométrica do reparo ósseo em tíbias de ratas tratadas com ácido zolendrônico - Germano, Evandro José (2015)
The objective of the research was to perform histomorphometric analysis of bone formation in defects created in tibias experimentally treated rats zolendronic acid by intravenous route. For this we used 20 adult albino rats (Rattus norvegius albinus, Wistar), which were divided into two groups according to treatment: Control Group (GC) – animals submitted to the creation of the bone defect (2 mm diameter by 4mm depth) without administration of zolendronic acid; and Experimental Group (GE) - animals submitted to the creation of the bone defect (2 mm in diameter and 4 mm deep) and administration of zolendronic acid. The animals were submitted to the EG biweekly administrations intravenous zolendronic acid at a dose of 0.035 mg / kg for 8 weeks and after surgical procedures administrations continued until the last trial. Bilateral bone defects in the tibia of the animals in both groups were prepared (n = 40). After periods of 14 and 28 days post surgery, animals were euthanized for removal of specimens. After obtaining the specimens followed by the histological processing for paraffin embedding and later histomorphometric analysis and statistical analysis using nonparametric Mann-Whitney test (α = 5%). The GC group had higher bone formation compared to the GE group, with a statistically significant difference in 14 days.